(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
the research approaches the auditory forms that indicate interjection in Al Mutantbi verse.It starts with tackling the concept of audition in language and terminology mentioning the views of those who handled this matter. Besides, it approaches the forms of auditory interjection through defining them and mentioning the various and most important ones like interrogation, origins, oath, call and many others. Then the research handles the functional use of these forms by AL MUTANTBI within his poetic contexts which indicate astonishment and marvel.